A new design of Lambertson magnet with true zero field region. (27th May 2020) - Zhao, Rongjie; Gu, Ming; Wang, Dong
Abstract: Lambertson magnet is an indispensable device in the beam injection and extraction scheme and the beam distribution system of nowadays big scientific facilities especially the synchrotron radiation facilities and Free Electron Lasers (FELs). It provides a field free region as the straight beam passing way, whereas the leakage field cannot be completely shielded. Instead of implementing high permeability material or complex gap structures to partially shield the leakage field, a new way by adding coils in the field free region is introduced in this paper. Results show that the added coils can reshape the leakage field to be a quadrupole field, so the leakage field at the magnetic center can be reduced to zero. It is the first time to combine the design of Lambertson magnet with quadrupole magnet and get the ideal field free region. The zero field point is also adjustable by changing the added coils current, which reduces the installation difficulty of Lambertson magnet to a great degree.